2019
DOI: 10.1186/s12893-019-0513-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-adjusted Charlson Comorbidity Index (ACCI) is a significant factor for predicting survival after radical gastrectomy in patients with gastric cancer

Abstract: Introduction To assess the ability of the Age-Adjusted Charlson Comorbidity Index (ACCI) to predict survival after radical gastrectomy in patients with gastric cancer (GC). Method Data from patients with GC who underwent radical gastrectomy from January 2008 to December 2012 in Fujian Medical University Union Hospital were retrospectively analyzed. Patients were categorized into either high ACCI group or low ACCI group based on the effect of ACCI on long-term GC prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 42 publications
5
46
0
Order By: Relevance
“…In addition, the 5-year RFS was 83.1% in the low-ACCI group and 73.4% in the high-ACCI group (HR=1.44, 95%CI=1.15-1.80, p=0.001). Lin et al evaluated the clinical impact of ACCE in 1476 gastric cancer patients who received curative surgery (18). They reported that there were significant differences in the OS between the low-and high-ACCI groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the 5-year RFS was 83.1% in the low-ACCI group and 73.4% in the high-ACCI group (HR=1.44, 95%CI=1.15-1.80, p=0.001). Lin et al evaluated the clinical impact of ACCE in 1476 gastric cancer patients who received curative surgery (18). They reported that there were significant differences in the OS between the low-and high-ACCI groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously explored the appropriate cut-off value of ACCI in several cancers. In the gastrointestinal region, Lin et al set 3 as the cut-off value in 1476 gastric cancer patients, and Maezawa et al set 6 as the cut-off value in 2254 gastric cancer patients (17,18). In the hepato-biliary pancreatic cancer region, Qu et al set 4 as the cut-off value in 268 intrahepatic cholangiocarcinoma patients, and Takahara et al set 5 as the cut-off value in biliary tract cancer (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The Charlson Comorbidity Index (CCI) is a validated numerical measure of the burden of chronic disease, originally developed to predict prognosis of patients with comorbidities. The ageadjusted CCI (ACCI) has been demonstrated to predict the incidence of postoperative complications following radical gastrectomy for gastric cancer, with a high ACCI score an independent risk factor for the long-term prognosis of gastric cancer patients after surgery (30). This could prove a useful measure in the decision to undergo surgery and to plan the therapeutic strategy by the multidisciplinary team.…”
Section: Surgerymentioning
confidence: 99%
“…The older patients presented with the burden of cardiovascular, endocrine and renal co-morbidity far in excess of that seen in younger patients, as evidenced by a signi cantly higher CCI [14][15][16]. While a direct correlation has yet to be studied between aaCCI and morbidity and mortality following emergency cholecystectomy, strong evidence exists supporting aaCCI as a robust predictor of poor outcomes following elective gynecologic, oncologic gastrointestinal and emergency orthopedic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The role of frailty as an independent risk factor for adverse postoperative outcomes is also now emerging [10][11][12][13]. An ageadjusted Charlson co-morbidity index [14][15][16] has been recently validated, while limitations in the discriminating power of the prognostic p-POSSUM score have been recognised in the older patient [17]. management of these patients [18,19].…”
Section: Introductionmentioning
confidence: 99%